2014
DOI: 10.1371/journal.pone.0086902
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a Determinant of Blood Pressure in Older Koreans: Findings from the Korea National Health and Nutrition Examination Surveys (KNHANES) 2008–2010

Abstract: BackgroundBlood pressure (BP) is directly and causally associated with body size in the general population. Whether muscle mass is an important factor that determines BP remains unclear.ObjectiveTo investigate whether sarcopenia is associated with hypertension in older Koreans.ParticipantsWe surveyed 2,099 males and 2,747 females aged 60 years or older.MeasurementsSarcopenia was defined as an appendicular skeletal muscle mass divided by body weight (ASM/Wt) that was <1 SD below the gender-specific mean for you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
145
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 26 publications
(32 reference statements)
5
145
0
5
Order By: Relevance
“…Thus, visceral fat could increase, although body weight decreased. Sarcopenic obesity is associated with hypertension [35] and CVD [36]. In fact, the individuals who transitioning from MHO to MAO phenotype were older and had higher blood pressure (data not shown).…”
Section: Wwwscidocorg/ijdvrphpmentioning
confidence: 91%
“…Thus, visceral fat could increase, although body weight decreased. Sarcopenic obesity is associated with hypertension [35] and CVD [36]. In fact, the individuals who transitioning from MHO to MAO phenotype were older and had higher blood pressure (data not shown).…”
Section: Wwwscidocorg/ijdvrphpmentioning
confidence: 91%
“…After adjusting for confounding factors the group with SO showed a higher chance of dyslipidemia (OR, 2.82; 95% CI, 1.76-4.51) regardless of sex (15). Many cross-sectional studies in the Korean population, especially in elderly subjects (7,10,14,43,44), but also in adults (11,12,45), showed that SO was associated with changes in the lipid profile characterized by elevated levels of triglycerides (TGL) (7,10,14,22,(43)(44)(45), total cholesterol (TC) (22) and reduction of the high density lipoprotein (HDL) (10,11). They used as criterion for diagnosis of sarcopenia, ASM adjusted for body mass and for obesity, BMI > 25 kg/m 2 , the visceral fat area (VFA) by computed tomography (CT) or waist circumference (WC).…”
Section: So and Risk Factors For Cardiometabolic And Cardiovascular Dmentioning
confidence: 99%
“…The association between SO and insulin resistance was described, only in women (11), male (12) or in the both sexes (3,7,9,14,15,43,44). All these studies used HOMA-IR (homeostatic model assessment insulin resistance) to investigated insulin resistance, but different methodologies were used to evaluate sarcopenia: ASM adjusted for body mass (7,11,12,14,15,43,44) or height (9), muscular area in the thigh/visceral fat (3) and the MM index (DEXA) (11) and BMI (12,14,15,43,44), VFA (3,7,11) and WC (9) for evaluate obesity. Individuals with SO showed a higher HOMA-IR when compared to others who were obese, sarcopenic or normal individuals (3,7,9,11,12,14,15,43,44).…”
Section: So and Risk Factors For Cardiometabolic And Cardiovascular Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Uma das doenças cardiovasculares que está associada ao processo de envelhecimento e sarcopenia é a HAS (CHUNG et al, 2013;HAN et al, 2014;PARK et al, 2013 …”
Section: Senescênciaunclassified